Research priorities and identification of a health‐service delivery model for psoriasis from the UK Psoriasis Priority Setting Partnership. (1st March 2021) - Ismail, D.; McAteer, H.; Majeed‐Ariss, R.; McPhee, M.; Griffiths, C. E. M.; Young, H. S.
Summary: Background: Psoriasis impacts the health and psychosocial functioning of patients, conferring a significant economic burden on healthcare systems. There remain unmet needs in psoriasis care, which if addressed by research, could improve clinical outcomes. Aim: To research priorities and identify a health service delivery model from the UK Psoriasis Priority Setting Partnership (PsPSP). Methods: Between July 2017 and November 2018, we invited people with lived experience of psoriasis and healthcare professionals to (i) identify unmet needs, and (ii) prioritize the order in which these should be addressed by research. We collaborated with the Psoriasis Association and used methodology established by the James Lind Alliance, which pioneers the joint setting of research priorities by patients and clinicians worldwide. Results: In our initial harvesting survey (Survey 1), 2133 questions were submitted by 805 individuals. Submissions that had not been answered by research (true uncertainties) were supplemented with evidence gaps from systematic reviews/guidelines published in the previous 5 years and refined to produce 55 indicative questions. Voting in Survey 2, by 1154 individuals, enabled a shortlist of questions, which were prioritized during the final workshop to produce a top 20 list of research questions. Submissions on health service delivery (5.8% of the total submissions), which were analysed separately, described a blueprint for psoriasis care. Conclusions: The PsPSP will inform the translational research agenda, ensuring that future research is relevant for the needs of people with psoriasis and those who manage the disease. Submissions on health service delivery describe a model of holistic, patient‐focused care providing high‐quality, effective management for patients with psoriasis.